Negotiating Marriage: Before, During, After - Johansen, Hanne Marie (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2005)
What does it means to negotiate marriage? According to the Longman Synonym Dictio-nary the meaning of the word negotiate is complex: “Bargain, make a deal, go back and forth, give and take, compromise, meet halfway, agree on, settle differences, settle, come to terms, contract, conclude, complete, finish.” The Merriam-Webster Dictionary of Synonyms and Anto-nyms mentions that negotiating is connected to arrange: “Negotiate, arrange mean to bring about through an exchange of views and wishes and agreement reached by bargaining and compromise … . Negotiate suggests that the dealings are carried on by diplomatic, business, or legal agencies …”, and “Arrange implies dealings intended for the restoration or establishment of order of those carried out between private persons or their representatives… Arrange a marriage as they did long ago”. Couples today negotiate their relationships and their marriage contract over and over again. They ask: what are my obligations – what are yours? In what way shall we take care of our children? How much time shall we spend outside the home, and as wage earners? What is best, to share property and income, or to retain separate economy and property? There are many de-manding tasks to fulfill in a modern marriage. A critical point is this: Is there really time for sex? Problems and tensions easily arise. Perhaps husband or wife finds comfort in alcohol, or through involvement in extramarital affairs. Some husbands even ventilate their frustration by the use of violence against the spouse and the children. When communication and negotiating fail in the private sphere, there is a good chance that things may go so wrong that negotiating has to con-tinue in the public sphere. Marriage counseling could be a solution or the case ends up in court. As mentioned in the dictionary negotiating may imply that the dealings are carried out by legal agencies. The negotiating couple has to decide on child custody and on how to share belongings and property. The concept “negotiating” is central in the study of modern marriage. Is this also true when we are concerned with the institution of marriage in the early modern period? In the extensive literature on gender and the family in early modern Europe, the study of marriage trouble, marital breakdowns and marriage negotiations have received increasing attention and, as a consequence, the topic of how marriage was negotiated in a legal and public setting has also been explored. The context is then both legal history and history of family and of gender.